The GA Future - Gans, Eric Lawrence (2020)
Faintly detectable signs suggest to me that perhaps the time is coming in which GA can play a significant role in the world’s intellectual life. As I have pointed out in a few recent Chronicles, GA, which emerged as French Theory was reaching its end, brings together the key ideas of Girard and Derrida, the...